Implementation of Teacher Professional Ethics in Social Media Activities in the Digital Era - Indah Ayu Febriana; Nur Khasanah; Nafila Mubarokah Mubarokah; zidan el zaldie (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to examine the normative basis of teacher professional ethics based on Law Number 14 of 2005 and examine its implementation in the use of social media in the digital era. The study uses a qualitative descriptive approach through a literature review by examining various regulations and relevant scientific literature from the past ten years. The results of the study indicate that teacher professionalism is not only determined by mastery of pedagogical, professional, social, and personality competencies, but also by moral integrity and adherence to the professional code of ethics. Technological developments expand ethical practices into the digital realm, presenting both opportunities and challenges, particularly regarding behavior on social media and student data protection. The government has responded by developing digital ethics guidelines, strengthening literacy through professional development programs, and providing protection and law enforcement mechanisms. Although their implementation still faces obstacles such as the digital literacy gap, limited access to training, and less than optimal dissemination of regulations. Therefore, ongoing strengthening efforts are needed through improving digital ethics competencies, establishing a school culture based on moral values, and collaboration between the government, professional organizations, and educational units. This study confirms that teaching professional ethics in the digital era is an inseparable part of adaptive professionalism, while adhering to humanitarian values and moral responsibility. Keywords: teaching professional ethics, professionalism, social media, digital literacy, education policy.